Chagas disease in an area of recent occupation in Cochabamba, Bolivia - Albarracin-Veizaga Hugo; Carvalho Maria Esther de; Nascimento Elvira M M do; Rodrigues Vera Lúcia C C; Casanova Cláudio; Barata José Maria S (Revista de Saúde Pública, 1999)
INTRODUCTION: A descriptive, entomological and seroepidemiological study on Chagas disease was conducted in a place of recent occupation on the outskirts of Cochabamba, Bolivia: Avaroa/Primer de Mayo (population:3,000), where the socio-economic level is low and no control measures have been made available. METHODS: The immunofluorescent antibody test (IFAT) was used for IgG and IgM anti-Trypanosoma cruzi antibodies in filter paper bloodspot eluates from 128 subjects (73 females, 55 males) selected by systematic sampling. Concerning each subject age, gender, birthplace, occupation, duration of residence and building materials used in their houses were recorded. Vectors were captured both in domestic and peridomestic environments. RESULTS: Seropositive, 12.5% (16/128): females, 15.1% (11/73); males, 9.1% (5/55). Average time of residence: 6.1 years for the whole population sample and 7.4 years for the seropositive subjects. Most houses had adobe walls (76.7% , n= 30), galvanized iron rooves (86.7%) and earthen floors (53.4%) 80% of the walls had crevices. One hundred forty seven specimens of Triatoma infestans were captured, of which 104 (70.7%) were domestic, and 1 peridomestic Triatoma sordida. Precipitin host identification: birds, 67.5%; humans, 27.8%; rodents, 11.9%; dogs, 8.7%; cats, 1.6%. House infestation and density indices were 53.3 and 493.0 respectively. We found 21 (14.3%) specimens of T. infestans infected with trypanosomes, 18 (85.7%) of which in domestic environments. DISCUSSION: The elements for the vector transmission of Chagas disease are present in Avaroa/Primer de Mayo and the ancient custom of keeping guinea pigs indoors adds to the risk of human infection. In neighboring Cochabamba, due to substandard quality control, contaminated blood transfusions are not infrequent, which further aggravates the spread of Chagas disease. Prompt action to check the transmission of this infection, involving additionally the congenital and transfusional modes of acquisition, is required.